Ultimate strength assessment of steel stiffened plate structures with grooving corrosion damage. (1st July 2015) - Wang, Yikun; Wharton, Julian A.; Shenoi, R. Ajit
Highlights: New approach to numerically simulate grooving corrosion on stiffened steel plates. Weld connections, weld-induced residual stresses and initial deflections considered. Insights on the corrosion effect of load shortening curves and ultimate strength. Assessment of the generality of empirical formulas. Abstract: An approach to simulate the behaviour of steel stiffened plates subjected to weld-induced grooving corrosion using nonlinear finite element modelling is proposed. The model includes the effects of different initial geometric imperfections and weld-induced residual stresses. The influence of corrosion damage on the load shortening curves and ultimate strength is investigated. It is shown that grooving corrosion depth has a greater influence on structural performance as compared with corrosion width for the same volume loss. Such corrosion damage could cause a significant reduction in the ultimate strength of a plate panel. Considerations of weld-induced deflection and residual stresses further enhance the corrosion influence on the strength capacity.